Nonepidermal members of the keratin multigene family: cDNA sequences and in situ localization of the mRNAs. - Knapp, B (1986)
A keratin set which consists of a type I 47kd and a type II 57kd protein occurs as a major constituent of the keratin patterns of various internal stratified epithelia of the mouse. We have isolated specific cDNA clones of the two complementary keratin subunits from a cDNA library constructed with polyA+RNA of mouse tongue epithelium and present the complete nucleotide and deduced amino acid sequences of the 57kd protein and about 75% of the corresponding data of the 47kd protein. The comparison of the sequence data with those of known epidermal keratin mRNAs coding for the two types of keratin proteins reveals a fundamentally identical and type-specific organization of the mRNAs into both highly conserved and variable domains. In order to avoid cross-reactions with other members of the keratin multigene family, appropriately taylored 35S-labeled cDNA probes comprising the low and non-homologous 3' coding and noncoding domains of the mRNAs were used for in situ hybridization to tissue sections. The localization and distribution of the corresponding transcripts indicates a strongly compartmentalized keratin expression in mouse tongue epithelium.